Does Household Finance Affect the Political Process? Evidence from Voter Turnout During a Housing Crisis - McCartney, W Ben (Review of Financial Studies, 2021)
Abstract I examine the effect of house price declines on voter participation using a novel person-level panel data set. Contrary to what the “angry voter hypothesis” predicts, I find that a 10% decline in local house prices decreases the participation rate of the average mortgaged homeowner by 1.6 percentage points. Consistent with a financial distress channel, house price declines have no effects on renters and particularly severe effects on highly leveraged households. My findings are consistent with the existence of a feedback loop between financial distress and inequality operating through voter participation.